Identifying quality responses using an analysis of response times: the RTcutoff function in R - Sideridis, Georgios; Alghamdi, Mohammed (Frontiers in Psychology, 2024)
The present study aims to develop an R function to develop and visualize thresholds that describe the response time of individuals in relation toconcerning their sample. The function utilizes the cumulative proportion correct (CUMP) approach, to estimate item-specific time threshold, which originated in the work of Guo and his colleagues. Besides the CUMP approach, the present function presents response time profiles on a measure using the mean of the sample and +1SD times so that it can discern between thoughtful engagement and processing with an item (termed problem-solving behavior) and rapid responding, guessing, and disengagement with the test. The advantage of the CUMP model utilized here is that it simultaneously engages both response time and response correctness to establish thresholds that differentiate engaged from disengaged participants. Given data on a measure in of reading comprehension for students in Saudi Arabia (n=494) using the Progress in International Reading Literacy Study (PIRLS 2021) international assessment, high and low low-achieving individuals that engaged in different behavior patterns were identified and plotted against their sample. Results pointed to the importance and necessity of the RTcutoff function to identify variable forms of engagement that have implications for personscore validity but also have implications for test validity and the need to increase measurement precision.